Franz-Keldysh effect of Ge-on-Si pin diodes at common chip temperatures - Schmid, M.; Kaschel, M.; Gollhofer, M.; Oehme, M.; Werner, J.; Ulbricht, K.; Kasper, E.; Schulze, J. (Proceedings of SPIE - The International Society for Optical Engineering, 2013)
This work concentrates on the device characteristics and performance of Ge-on-Si p-i-n diodes for the use as absorption modulators. At first, the impact of temperature on electrical and on optical characteristics of these p-i-n diodes is investigated. Secondly, the feasibility of optical modulation using the Franz-Keldysh effect is demonstrated for temperatures up to 359 K. The Ge-on-Si p-i-n diodes are grown using a molecular beam epitaxy system. The layer structure includes a double Si/Ge-heterojunction and an intrinsic zone with a thickness of 500 nm. During the growth process several annealing steps are performed to reduce the dislocation density and incorporate tensile strain in the intrinsic zone. The dark current is proportional to the diode area and amounts to 40 mA/cm2 at a reverse voltage of 1 V. An analysis of the temperature dependence of the dark current shows that it is dominated by generation/recombination of carriers probably at threading dislocations. The optical absorption spectra recorded show a shrinkage of the infrared cut off wavelength of about 0.6 nm/K. In addition the change of absorption at the direct bandedge with different applied biases, i.e. the Franz-Keldysh effect, is demonstrated for temperatures from 300 K to 359 K. With regard to modulation of an optical signal the on/off ratio is evaluated as function of the voltage swing. With a moderate voltage swing of 2 V the maximal absorption change is 300 cm-1 and the optimal working regime shifts from 1625 nm at 300 K to 1665 nm at 337 K. © 2013 SPIE.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Franz-Keldysh effect; Germanium-on-Silicon; Photodiode; Silicon photonics; Temperature dependence